Deposição da calda de pulverização na cultura da soja em função do tipo de ponta e do volume aplicado - Hartmann-Schmidt, Michele Alessandra (2006)
To prevent the losses in agriculture has been the great objective of the Engineers Agronomists, as well as professionals of other similar areas of agrarian sciences that are worried very about the losses in agriculture, including the fitossanitária area. Most of the time, during the chemical control of plagues, harmful illnesses and plants, give to much importance to the fitossanitário product and little attention to the application technique. The consequence is the loss of effectiveness, when not total it failure of that take to the loss of yield of the cultivate and the damages to the environment and the proper health human being. The majority of the applications of agricultural defensives is made by means of spraying, that is, for the generation and emission of liquid particles. Due to those needs the present work was carried out in Cascavel PR, in the harvest 2004/2005, using the soybean cultivar CD 202, with the objective evaluating the amount of syrup deposited on the soybean leaves, varied the volume of syrup applied and the beaks types used in the spraying bar, used tracer substance, simulating the physical characteristics of the solutions of the products. To evaluate the spraying distribution, fifteen leaves were collected per plant in different extracts (higher, medium and lower), with the purpose of evaluating the syrup penetration, in agreement with the different beaks and applied volumes. The experimental design was arranged in randomized complete blocks, in factorial arrangement, with four beaks and point of the type simple fan, double fan, double fan with air injection and empty cone and 3 syrup volumes (150, 250 and 350 L ha-1). In agreement with the results obtained and in the conditions that the present work was carried out. In accordance with the results gotten and in the conditions where the present work was lead, concluded that: In what it says respect to the peaks of spraying in different extracts of the plants, can be concluded that, it did not have significant difference enters the used peaks in the experiment. As for the volumes of syrup volume, it did not have significant difference between the same ones, however when compared in different extracts of the plant, the biggest deposition L was gotten with the use of 250 ha-1, having been that when the volume for more varied or for less the deposition it was lesser. As for the extract of the plant, the deposition of syrup volume varied of decreasing form of the superior extract the inferior